Usaha Meningkatkan Pendapatan Mitra Melalui Rekayasa Mesin Pencacah Makanan Ternak di Karanganyar - Y Yulianto Kristiawan; Suhartoyo (ULINA: Jurnal Pengabdian kepada Masyarakat, 2023)
The problem faced by breeders is regarding feed that comes from green leaves. Green leaf feed is a feed that is very popular with cows because it has a high nutritional content and helps significant growth when compared to cows that are only fed products other than leaf greens. The problem faced is green leaf feed if it is not cut into small pieces and not uniform, sometimes cows are lazy to eat and eventually produce waste, if leftovers are left it will produce disease and on the other hand, wasteful feed. The results of discussions with SMEs of cattle breeders require a chopping machine that is easy to operate, the results can be good, safe for humans and low operating costs. The machine can chop to a uniform size and doesn't smell like a machine, so the cows want to eat it with gusto. The specifications of the machine handed over to the cattle breeder UKM are as follows. The machine handed over is a cruiser machine using 4 blades with a blade length of 25 cm, a width of 4 cm and a thickness of 3 mm of hardened steel. Construction height 1400 mm, width 800 mm and 600 mm, blade diameter 500 mm, Single phase 350 Watt electric motor, motor speed: 1450 rpm, engine speed 750 rpm.